2020
DOI: 10.3340/jkns.2018.0177
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes According to Dekyphosis in Patients with Ossification of the Posterior Longitudinal Ligament in the Thoracic Spine

Abstract: Objective : Ossification of posterior longitudinal ligament (OPLL) in the thoracic spine may cause chronic compressive myelopathy that is usually progressive, and unfavorable by conservative treatment. Although surgical intervention is often needed, the standard surgical method has not been established. Recently, it has been reported that posterior decompression with dekyphosis is effective surgical technique for favorable clinical outcome. The purpose of this study was to evaluate the surgical outcomes in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] The literature notes numerous advantages of RA over general anesthesia (GA), including favorable perioperative hemodynamic stability, reduced mortality, intraoperative blood loss, arterial and venous thrombosis, pulmonary embolism, myocardial infarction, renal failure, and decreased incidence of cognitive dysfunction. [9][10][11][12][13][14][15] Even though RA is widely accepted in other fields, the use of RA during elective lumbar surgery failed to gain wide acceptance. [1][2][3][4][5]16 GA is the preferred and most commonly used anesthesia technique for lumbar spine surgery such as microdiscectomy or lumbar decompression.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The literature notes numerous advantages of RA over general anesthesia (GA), including favorable perioperative hemodynamic stability, reduced mortality, intraoperative blood loss, arterial and venous thrombosis, pulmonary embolism, myocardial infarction, renal failure, and decreased incidence of cognitive dysfunction. [9][10][11][12][13][14][15] Even though RA is widely accepted in other fields, the use of RA during elective lumbar surgery failed to gain wide acceptance. [1][2][3][4][5]16 GA is the preferred and most commonly used anesthesia technique for lumbar spine surgery such as microdiscectomy or lumbar decompression.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various surgical approaches developed to address T-OPLL, posterior decompression with instrumented fusion (PDF) has emerged as an increasingly popular method. This preference is due to its positive results in reducing symptoms and its relatively low complication rate, as supported by numerous studies [1,3,[9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 96%
“…3,4 Two centuries have passed since the discovery of this disease, and nearly a century has passed since the specific form of the disease was confirmed, but we still do not know the exact cause, pathogenesis, and treat-ment of OPLL. [5][6][7][8] Numerous studies over the last several decades have suggested the involvement of multiple etiologic factors in the development of OPLL, including genetic factors, mechanical stress, nutrition, and secondary changes caused by systemic disease. 9 With regard to the pathogenesis of OPLL, on one hand, OPLL demonstrates racial differences in its incidence, which is especially high in East Asian males.…”
Section: Introductionmentioning
confidence: 99%
“…OPLL was first reported by Key in 1838 and described in detail by Tsukimoto in 1960 [ 3 , 4 ]. Two centuries have passed since the discovery of this disease, and nearly a century has passed since the specific form of the disease was confirmed, but we still do not know the exact cause, pathogenesis, and treatment of OPLL [ 5 - 8 ]. Numerous studies over the last several decades have suggested the involvement of multiple etiologic factors in the development of OPLL, including genetic factors, mechanical stress, nutrition, and secondary changes caused by systemic disease [ 9 ].…”
Section: Introductionmentioning
confidence: 99%